VERBA EMOTIF BAHASA MELAYU DIALEK KETAPANG KAJIAN SEMANTIK - Muhammad Setiawan; Amriani Amir; Agus Syahrani (Universitas Tanjungpura, 2019)
AbstractThe Dialect of Ketapang Malay is one of the regional languages in West Kalimantan, precisely in Matan Hilir Subdistrict, Ketapang District. BMDK is used to communicate in daily life and in official events, in which it is used in traditional cases, traditional ceremonies, and preservation of regional culture in the form of poetry, rhymes, folklore, and songs. This research is related to linguistics. This research is focused on the semantic field about emotive verbs, which is one of the other verbs. In general the problem in this study is